2019
DOI: 10.1111/apa.14937
|View full text |Cite
|
Sign up to set email alerts
|

No significant associations between breastfeeding practices and overweight in 8‐year‐old children

Abstract: Aim The aim was to examine if breastfeeding practices were associated with body mass index (BMI) and risk of overweight or obesity in third grade (8 years) of elementary school. Methods In a regional cohort, we related BMI z‐scores and presence of overweight or obesity at 8 years of age with ever being breastfed and with duration of exclusive and partial breastfeeding after adjusting for potential confounders. Parents completed questionnaires on breastfeeding and sociodemographic and lifestyle factors at schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 25 publications
0
13
0
4
Order By: Relevance
“…Thirty articles, published between 2003 and 2019, were identified that met the inclusion criteria and examined ever, compared with never, consuming human milk and overweight and/or obesity. [1][2][3][4][5][6][7][8][9][10][11][14][15][16][17][19][20][21][22]26,27,[30][31][32][35][36][37][39][40][41] They presented evidence from 21 independent studies. Four of the 21 studies were also described in the section about evidence from siblings (i.e., Linked CENTURY Study, Children of NLSY79, Add Health, and CDS).…”
Section: Child Development Supplement Of the Panel Study Of Income Dynamics (Cds)mentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty articles, published between 2003 and 2019, were identified that met the inclusion criteria and examined ever, compared with never, consuming human milk and overweight and/or obesity. [1][2][3][4][5][6][7][8][9][10][11][14][15][16][17][19][20][21][22]26,27,[30][31][32][35][36][37][39][40][41] They presented evidence from 21 independent studies. Four of the 21 studies were also described in the section about evidence from siblings (i.e., Linked CENTURY Study, Children of NLSY79, Add Health, and CDS).…”
Section: Child Development Supplement Of the Panel Study Of Income Dynamics (Cds)mentioning
confidence: 99%
“…Thirty articles presented evidence from 21 independent studies about the relationship between ever, compared with never, consuming human milk and overweight and/or obesity at 2 years of age and older. [1][2][3][4][5][6][7][8][9][10][11][14][15][16][17][19][20][21][22]26,27,[30][31][32][35][36][37][39][40][41] A synthesis and assessment of the evidence follows.…”
Section: First Baby Study (Fbs)mentioning
confidence: 99%
See 2 more Smart Citations
“…Bjertnæs et al examined whether breastfeeding was associated with body mass index (BMI) and the risk of overweight or obesity in a regional Norwegian cohort of 8‐year‐old children. They found that 90% had been breastfed, but the adjusted analyses of the BMI scores were not significantly related to breastfeeding.…”
Section: No Association Between Breastfeeding and Being Overweight Atmentioning
confidence: 99%